REPRESENTASI KONSEP DIRI SEORANG TRANSSEKSUAL DALAM FILM THE DANISH GIRL - Chealsie Alicia Tjhen; Cendera Rizky Anugrah Bangun (Metacommunication: Journal of Communication Studies, 2022)
Film has a role as a representation to reflect and reality in society. One of these realities is the transsexual phenomenon and the self concept that transsexual people themselves go through. Self concept can be defined as people’s image of themselves. In this study, the researcher wanted to see the self concept of being transsexual in the film The Danish Girl. The approach used is qualitative, Media Text Analysis (MTA), with the John Fiske semiotic method and the constructivist paradigm, also the Queer ideology. In analyzing the representation of self concept in being a transsexual person, the researcher applied three certain levels, namely the level of reality, the level of representation, and the level of ideology. The results showed that there was a self concept representation of being a transsexual person who featured the main character in the film The Danish Girl. These findings refer to a number of signs, both verbally and nonverbally, including the concept of self concept ideology itself. Kata kunci: Konsep diri, representasi, transseksual, semiotika, John Fiske